HUBUNGAN PERILAKU MEROKOK ORANG TUA DENGAN KEJADIAN ISPA PADA BALITA DI WILAYAH KERJA PUSKESMAS REMBANG KABUPATEN PURBALINGGA 2012 - Yuli Trisnawati Trisnawati; Juwarni Juwarni (Kesmas Indonesia, 2013)
ABSTRACT Acute Respiratory Infections (ARI) is acute inflammation of the upper and lower respiratory tract. One risk factor for ARI were behavioral factors of smoking parents in at home. These habits can have a negative impact, especially family members on ISPA insident on toddler. The purpose of this research is to finding out correlation to find parent smooking behavior to find ARI insident between Toddlers at Working area of Public Health Center Rembang on Purbalingga district at year 2012. This study is an analytical survey research with case-control approach. Simple Random Sampling technique with count of sample between 102 respondents (case and control). Research instrument in the form of questionnaires and data analysis was performed using univariate and Chi-Square for bivariate. Parental smoking behavior in the Work Area Public Health Center In 2012 Purbalingga were heavy categorized (80.4%). There were correlation between parent smoking behavior on ARI insident at toddler (p=0.000, OR=13.3 95%CI 5.17-34.345). Keyword : smooking behavior, ARI Kesmasindo, Volume 6,( 1 ) Januari 2013, Hal. 35-42